The Challenges of Empowering Women: The Experience of Pulse Innovation Project in Southern Ethiopia - Esayas Bekele Geleta; Paitence Elabor-Idemudia; Carol Henry; Nigatu Reggassa (SAGE Open, 2017)
Within the last two decades, women’s empowerment has been the central theme of international development policy and practice. This article seeks to elucidate the challenges of integrating gender in a development project to empower women. Drawing on the wider literature on women’s empowerment, it constructs a framework to analyze the meaning of empowerment. The article then draws on the framework and empirical data gathered to illuminate the challenges of integrating gender in a pulse innovation project, implemented in Southern Ethiopia. The article elucidates gender hierarchies that limit the extent of women’s involvement in crop production processes. It demonstrates social and cultural factors that restrict women from fully participating in high value pulse markets and their involvement in production and exchange decision-making. It also illustrates how existing social networks, relations, and links disadvantage women. The article then recommends solutions to help facilitate the integration of gender in the project toward the empowerment of women.